UPAYA PENANGULANGAN LIMBAH MINYAK JELANTAH PADA INDUSTRI KERUPUK JANGEK DI DESA SUNGAI RAJA LABUHANBATU - Putri Cahaya Situmorang; Martha Rianna; Zikri Noer; Doni Aldo Samuel Siahaan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Almost all families have used cooking oil at home. Used cooking oil includes domestic waste generated from cooking and frying food using high temperatures. This Community Service Partner is the Jangek Cracker Business in Sungai Raja Village, Sumberjo Hamlet, Na.IX-X District, North Labuhanbatu Regency, North Sumatra, Indonesia produces quite a lot of waste cooking oil every day. The partner's problem is that the business owner uses a large enough amount of cooking oil every day and throws the waste into the ditch. 66% of the people of Sungai Raja Village who live around the factory use cooking oil every day, of which 80% of the people use waste cooking oil more than 3 times. Only 2% of the people know that waste cooking oil can be recycled into products with economic value and 98% of people throw away waste cooking oil carelessly. The conclusion of this community service is to educate about the dangers and impacts of waste cooking oil on the environment and health and make new innovative products from waste cooking oil with economic value such as aromatherapy candles and bath soaps.